A comparative assessment of metals and phthalates in commercial tea infusions: A starting point to evaluate their tolerance limits. (1st August 2019) - Troisi, Jacopo; Richards, Sean; Symes, Steven; Ferretti, Viviana; Di Maio, Antonietta; Amoresano, Angela; Daniele, Bruno; Aliberti, Francesco; Guida, Marco; Trifuoggi, Marco; De Castro, Olga
Highlights: Metals and phthalates concentrations were determined in 32 commercial tea packages. Average daily intake of metals and phthalates has been estimated. Associated Hazard Quotients (HQ) were calculated to determine daily risk of health. The study is a starting point to evaluate limits of metals/phthalate in tea. Abstract: Tea is one of the most consumed beverages in the word. Here we report the concentrations of metals and phthalates in 32 commercial tea packages. The data were used to estimate the average daily intake of metals and phthalates, and associated Hazard Quotients (HQ) were calculated in order to determine risk of non-cancerous health effects for adults consuming tea on a daily basis. Tea samples were chosen based on the sales network, the price, the marketing quality and the presence of filters in the packages. Relatively high median concentrations of Al (5240 µg/L), Ni (44 µg/L), and Mn (2919 µg/L) were detected. No metals or phthalates quantified in the tea infusions and soluble tea showed an HQ greater than 1, indicating no risk of non-cancerous health effects. The data presented herein may serve as a starting point to evaluate tolerance limits of metals and phthalate in the tea infusion.